Effect of mixing ingredient on workability and compressive strength of palm oil clinker lightweight concrete containing palm oil fuel ash - Khairunisa, Muthusamy; Nur Azzimah, Zamri; Andri, Kusbiantoro (TULPAR Academic Publishing, 2018)
Palm oil industry is one of the important industry that contribute to the country’s prosperity. This flourishing industry however also causes environmental problems namely air pollution, soil degradation as well as water pollution due to waste disposal issue. At the same time, intensive cement production and granite mining is damaging the environment and natural habitats. Hence, various efforts have been made by researchers to minimize the effect of pollution including integrating oil palm wastes in construction as building materials. In this study, granite aggregate was fully replaced by palm oil clinker (POC) in lightweight aggregate concrete production. In order to reduce the utilization of cement in concrete, palm oil fuel ash (POFA) was ground to improve its pozzolanic reactivity to partially replace cement in lightweight aggregate concrete. From this investigation, the best performance concrete was attributed by POC LWAC with 20% POFA when the water cement ratio and superplasticizer are 0.45 and 1.0%. Inclusion of water cement ratio and superplasticizer of 0.35 and 0.8% would adversely affects the workability and strength of POC LWAC with POFA.